Behavior Change Interventions to Reduce Illegal Fishing - Battista, Willow; Romero-Canyas, Rainer; Smith, Sarah Lindley; Fraire, Jose; Effron, Micah; Larson-Konar, Dylan; Fujita, Rod (Frontiers in Marine Science, 2018)
Illegal fishing is a serious problem that threatens the sustainability of fisheries around the world. Historically, policy makers and fishery managers have relied on the “deterrence model” to alleviate it. This approach focuses on the imposition of strict sanctions and relatively intensive monitoring and enforcement programs in an attempt to increase the costs of illegal behavior. However, while this sort of command-and-control approach can sometimes be successful in large-scale fisheries, small-scale fisheries rarely have the associated resources or necessary governance structures required, and thus strong and reliable monitoring and enforcement has proven to be an elusive goal. Beyond these top-down approaches, non-monetary factors, whether they are cultural, social or psychological, can also influence illegal fishing behaviors, either positively or negatively, and failing to address these factors can undermine the efficacy of an otherwise effective and well-designed fishery management system. Here we explore the use of strategies to reduce illegal fishing behaviors based on insights from behavioral science, in order to augment and secure the effectiveness of conventional deterrence strategies as well as to provide support for alternative means of deterring illegal fishing often required for small-scale fisheries. We draw on theory and studies from the behavioral science literature to show how successful behavior change interventions have been implemented in other sectors, and describe a process for designing interventions for changing specific illegal fishing behaviors. The process begins with an in-depth stakeholder characterization to capture existing norms, beliefs, and modes of thinking about illegal fishing as well as descriptions of specific illegal fishing behaviors. Potential interventions that may disrupt the beliefs, norms, and thought modes that give rise to these behaviors, along with those that encourage desirable behaviors, are developed by applying principles gleaned from the behavioral science literature. These “hypothetical interventions” are then tested using artefactual experiments, piloted with small groups of actual stakeholders and, finally, scaled such that illegal fishing is significantly reduced.